An experimental study on the mechatronics design and implementation of an intelligent active vibration control system for a CSLRFM - Moloody, Abbas; As’arry, Azizan; Sai Hong, Tang; Kamil, Raja; Md. Zain, Mohd Zarhamdy; Bahiuddin, Irfan (Semarak Ilmu Publishing, 2025)
This study enhances Robotics Flexible Manipulator (RFM) performance by developing a dynamic Mechatronics Test Rig System (MTRS) and a controller for a Combined Single-Link Robotics Flexible Manipulator (CSLRFM). RFMs offer benefits such as lighter weight and faster response but present challenges in motion and vibration control under disturbances. To address this, a Modified Differential Evolution Optimization Algorithm (MDEOA) tunes a PID controller to improve vibration suppression. Additionally, a New Gyroscopic Combined Actuator (NGCA) is introduced for Intelligent Active Vibration Control (IAVC). Comparing (AVC-DEO-PID) and (AVC-FL-PID) controllers with traditional PID, Fuzzy, and (Fuzzy-PID) controllers, the results show (AVC-DEO-PID) performs best, achieving up to about 93.471% faster rise and settling times, eliminating maximum overshoot, and reducing steady-state error by about 90-100%. It is 49-78% faster in peak time, with a 92% reduction in settling time, and shows 90-100% consistency across simulations and experiments. The modified algorithm demonstrates its potential in optimizing CSLRFM performance, making it a robust solution for real-time applications.